ISLAMIC PSYCHOTERAPHY AND SOCIAL DISRUPTION - Naharin - Suroyya (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
This paper uses the perspective of Islamic psychotherapy to examine the development of science and technology and its influence on the changes in adolescent life based on the values of the Qur’an and the Hadi>th. It particularly addresses the practice of Islamic counseling at an Islamic Junior Middle-School, Madrasah Tsanawiyah Negeri/MTsN 4. This article further argues the applicability of Islamic Psychotherapy as a model of overcoming crisis among the students through religious activities. Islamic psychotherapy dictates students to manage mind, emotion and ethics as well as to distance themselves from religiously unlawful acts. A series of collective Islamic rituals performed by students is crucial as a way to cultivate collective belongings, to maintain self-integrity, integrity of the soul and to achieve self-actualization.